2023
DOI: 10.1002/cbf.3865
|View full text |Cite
|
Sign up to set email alerts
|

Auranofin sensitizes breast cancer cells to paclitaxel chemotherapy by disturbing the cellular redox system

Deepika Natarajan,
N. Rajendra Prasad,
M. Sudharsan
et al.

Abstract: The intrinsic redox status of cancer cells limits the efficacy of chemotherapeutic drugs. Auranofin, a Food and Drug Administration‐approved gold‐containing compound, documented with effective pharmacokinetics and safety profiles in humans, has recently been repurposed for anticancer activity. This study examined the paclitaxel‐sensitizing effect of auranofin by targeting redox balance in the MDA‐MB‐231 and MCF‐7 breast cancer cell lines. Auranofin treatment depletes the activities of superoxide dismutase, cat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 59 publications
0
2
0
Order By: Relevance
“…It has been reported that auranofin displays anticancer activity against cancer cells through FOXO3 activation and the prevention of Nrf2 translocation to the nucleus 18 . Recently, we showed that auranofin treatment induces oxidative stress in the breast cancer cells which contributes for paclitaxel mediated apoptotic cell death 19 . In this present study, we elucidated the role of FOXO3/Nrf2/Keap1 signaling in the auranofin and paclitaxel mediated apoptotic cell death in the breast cancer cells.…”
Section: Introductionmentioning
confidence: 56%
See 1 more Smart Citation
“…It has been reported that auranofin displays anticancer activity against cancer cells through FOXO3 activation and the prevention of Nrf2 translocation to the nucleus 18 . Recently, we showed that auranofin treatment induces oxidative stress in the breast cancer cells which contributes for paclitaxel mediated apoptotic cell death 19 . In this present study, we elucidated the role of FOXO3/Nrf2/Keap1 signaling in the auranofin and paclitaxel mediated apoptotic cell death in the breast cancer cells.…”
Section: Introductionmentioning
confidence: 56%
“…18 Recently, we showed that auranofin treatment induces oxidative stress in the breast cancer cells which contributes for paclitaxel mediated apoptotic cell death. 19 In this present study, we elucidated the role of FOXO3/Nrf2/Keap1 signaling in the auranofin and paclitaxel mediated apoptotic cell death in the breast cancer cells.…”
mentioning
confidence: 83%